2022
DOI: 10.1007/s12185-022-03446-1
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for the treatment of chronic myeloid leukemia from the NCCN and ELN: differences and similarities

Abstract: Patients diagnosed with chronic myeloid leukemia (CML) in chronic phase can now have a life expectancy comparable to that of the general population thanks to the use of tyrosine kinase inhibitor (TKI) therapies. Although most patients with CML require lifelong TKI therapy, it is possible for some patients to achieve treatment-free remission. These spectacular results have been made possible by the development of superior treatment modalities as well as clinicians' efforts in strictly adhering to clinical guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 109 publications
1
15
0
Order By: Relevance
“…The frequency of monitoring after discontinuation is similar to that mentioned in the 2020 ELN guidelines; however, patients who remain in the MMR would require quarterly monitoring after the TFR should be attempted only if the condition of the patient with CML is well controlled. Currently, qRT-PCR is used internationally as the gold standard for detecting BCR::ABL transcripts, 15 and its detection results are used as important indicators for evaluating the efficacy and prognosis of patients with CML. Digital droplet PCR (ddPCR), which has emerged recently, uses a water-oil emulsion droplet system that divides the sample into thousands of individually repeated PCRs.…”
Section: Current Guidelines For Tfrmentioning
confidence: 99%
“…The frequency of monitoring after discontinuation is similar to that mentioned in the 2020 ELN guidelines; however, patients who remain in the MMR would require quarterly monitoring after the TFR should be attempted only if the condition of the patient with CML is well controlled. Currently, qRT-PCR is used internationally as the gold standard for detecting BCR::ABL transcripts, 15 and its detection results are used as important indicators for evaluating the efficacy and prognosis of patients with CML. Digital droplet PCR (ddPCR), which has emerged recently, uses a water-oil emulsion droplet system that divides the sample into thousands of individually repeated PCRs.…”
Section: Current Guidelines For Tfrmentioning
confidence: 99%
“…Landmark studies have indicated that discontinuing TKI is safe for patients with CML who have maintained a DMR for more than 2 years [4], ideally for more than 5 years [5]. International guidelines recommend quantitative reverse transcription-PCR (qRT-PCR) testing with a detection sensitivity lower than MR4.5 (0.0032% IS ) [2,3,6]. However, qRT-PCR has inherent limitations regarding its accuracy and sensitivity [7].…”
Section: Introductionmentioning
confidence: 99%
“…Most patients tolerate this treatment well, and hematological toxicities ameliorate rapidly following discontinuation or tapering of imatinib. 1,2 Prolonged myelosuppression has rarely been reported and develops usually several months after imatinib administration. [3][4][5][6][7][8][9] A newly diagnosed CML-CP patient developed prolonged severe myelosuppression (lasting for more than 3 months) following only one week of imatinib at 400 mg/day as the solitary treatment.…”
Section: Introductionmentioning
confidence: 99%